2015
DOI: 10.1111/ijcs.12165
|View full text |Cite
|
Sign up to set email alerts
|

Shopping online for goods vs. services: where do experiential features help more?

Abstract: This study investigates how the type of offer sold online (goods vs. services) moderates the relationships between perceived experiential values and customers' attitudes towards the website. A sample of 107 e-shoppers of services and 110 e-shoppers of physical goods responded to a survey on their most recent e-shopping experiences. Results support the majority of hypotheses. It was found that although offering experiential values on the site improves customers' attitudes for both physical goods and services we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
0
19
1
1
Order By: Relevance
“…Thus, indicating that emotional experience plays a very minimal role in the adoption of online shopping. This contrasts previous studies (e.g., Shobeiri et al, ) wherein aesthetics was found to be a better predictor of site attitudes than are service excellence and CROI but validates Rose et al () who found that aesthetics does not significantly relate to affective experiential state. Thus, consistent with the findings of Novak et al (), it was found that Nigerian e‐shoppers are more goal directed rather than hedonically driven.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Thus, indicating that emotional experience plays a very minimal role in the adoption of online shopping. This contrasts previous studies (e.g., Shobeiri et al, ) wherein aesthetics was found to be a better predictor of site attitudes than are service excellence and CROI but validates Rose et al () who found that aesthetics does not significantly relate to affective experiential state. Thus, consistent with the findings of Novak et al (), it was found that Nigerian e‐shoppers are more goal directed rather than hedonically driven.…”
Section: Resultscontrasting
confidence: 95%
“…Unlike other researchers (e.g., Babin et al, ; Novak et al, ), Mathwick et al () recognise that all the dimensions are experiential. Recent research (see Shobeiri, Mazaheri, & Laroche, ) adds empirical validity to this body of work. Jeong, Fiore, Niehm, and Lorenz () adopted and tested Pine and Gilmore's () four experiential realms (entertainment, educational, escapist, and aesthetic experiences) in the online shopping context.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Using data from Eurobarometer for France and West Germany, Sun (2011) examined the roles of experience and cultural propensity to trust in conducting e-commerce. The moderating role of the type of good sold (goods vs services) in the relationship between perceived experiential values and customer attitudes toward the website was studied by Shobeiri et al (2015). Although offering experiential values on the site improves attitudes for both products and services, the impact was much stronger in the case of services.…”
Section: Introductionmentioning
confidence: 99%
“…Digital vs non-digital) telah terbukti memengaruhi persepsi pembelanja tentang risiko sementara persepsi mungkin dipengaruhi tetapi dampaknya lebih kuat untuk layanan daripada produk (Shobeiri et al, 2015;Dai et al, 2014). Pandangan pembeli tentang nilai utilitarian dan nilai hedonis pada produk tertentu juga telah terbukti mempengaruhi preferensi saluran (Kushwaha dan Shankar, 2013).…”
Section: Keterbatasan Dan Penelitian DI Masa Depanunclassified